Preliminary exploration of the feasibility and safety of a novel magnetic ligation ring for hemorrhoid ligation: an experimental study based on canine rectal mucosal ligation procedure - Yang Zhigang; Xu Jiangtao; Liu Chenying; Lou Yamin; Cui Long; He Yongshan (结直肠肛门外科)
[Objectives] To preliminarily explore the feasibility and safety of using a novel magnetic ligation ring for hemorrhoid ligation. [Methods] Six adult Labradors were used. A disposable manual vacuum ligator was used to simulate hemorrhoid ligation on the canine rectal mucosa, employing novel magnetic ligation ring designed with the participation of our team and/or ordinary rubber ligation ring. According to the experimental study design, each dog received 8 ligation rings, resulting in a total of 29 novel magnetic ligation rings and 19 ordinary rubber ligation rings being applied across the 6 dogs. Two dogs received 8 novel magnetic ligation rings each, 1 dog received 8 ordinary rubber ligation rings, and the remaining 3 dogs underwent ligation with both types. The overall condition of the rectal mucosa ligation and the time until ring detachment were recorded (collecting feces to monitor detachment within 1 week post-operation), comparing the detachment time of different types of ligation ring. [Results] All 6 dogs successfully completed the planned rectal mucosa ligation procedure, and the operations were generally smooth. Post-operative conditions were good, with no significant abnormal activity observed in the dogs, and no evident blood in their feces. Some of the detached novel magnetic ligation rings were found to contain mucosal tissue. In 2 dogs that underwent ligation with both types of ligation ring, 1 ordinary rubber ligation ring was not retrieved from each dog. The average detachment time for the 29 novel magnetic ligation rings was (3.3±1.7) days, compared to (4.5±1.4) days for the 17 ordinary rubber ligation rings, with a statistically significant difference (P<0.05). For the 2 dogs that only received novel magnetic ligation rings, the average detachment time was (3.5±1.7) days for 16 rings; whereas for the dog that only received ordinary rubber ligation rings, the average detachment time was (5.3±1.1) days for 8 rings. [Conclusion] Under the conditions of this experimental study, novel magnetic ligation ring may offer a potential advantage in terms of detachment time when used for rectal mucosa ligation, compared to the ordinary rubber ligation ring.